Turing's legacy : developments from Turing's ideas in logic - Downey, R. G. (Rod G.) (Cambridge : Cambridge University Press, 2014)
Alan Turing was an inspirational figure who is now recognised as a genius of modern mathematics. In addition to leading the Allied forces' code-breaking effort at Bletchley Park in World War II, he proposed the theoretical foundations of modern computing and anticipated developments in areas from information theory to computer chess. His ideas have been extraordinarily influential in modern mathematics and this book traces such developments by bringing together essays by leading experts in logic, artificial intelligence, computability theory and related areas. Together, they give insight into this fascinating man, the development of modern logic, and the history of ideas. The articles within cover a diverse selection of topics, such as the development of formal proof, differing views on the Church-Turing thesis, the development of combinatorial group theory, and Turing's work on randomness which foresaw the ideas of algorithmic randomness that would emerge many years later.
Turing's legacy: developments from Turing's ideas in logic / Rod Downey -- 1. Computability and analysis: the legacy of Alan Turing / Jeremy Avigad and Vasco Brattka -- 2. Alan Turing and the other theory of computation (expanded) / Lenore Blum -- 3. Turing in Quantumland / Harry Buhrman -- 4. Computability theory, algorithmic randomness and Turing's anticipation / Rod Downey -- 5. Computable model theory / Ekaterina B. Fokina, Valentina Harizanov and Alexander Melnikov -- 6. Towards common-sense reasoning via conditional simulation: legacies of Turing in artificial intelligence / Cameron E. Freer, Daniel M. Roy, and Joshua B. Tenenbaum -- 7. Mathematics in the age of the Turing machine / Thomas C. Hales -- 8. Turing and the development of computational complexity / Steven Homer and Alan L. Selman -- 9. Turing machines to word problems / Charles F. Miller, III -- 10. Musings on Turing's thesis / Anil Nerode -- 11. Higher generalizations of the Turing model / Dag Normann -- 12. Step by recursive step: Church's analysis of effective calculability / Wilfried Sieg -- 13. Turing and the discovery of computability / Robert Irving Soare -- 14. Transfinite machine models / P.D. Welch.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Turing, Alan Mathison, -- 1912-1954.; Computational complexity; Machine theory